A call for strengthened evidence on targeted, non-pharmaceutical interventions against COVID-19 for the protection of vulnerable individuals in sub-Saharan Africa. (October 2020) - Colebunders, Robert; Siewe Fodjo, Joseph Nelson; Vanham, Guido; Van den Bergh, Rafael
Highlights: Curbing the transmission of SARS-CoV-2, the causative agent of COVID-19, may be difficult in sub-Saharan Africa. Overall COVID-19-related mortality remains low because of the young population. Protecting vulnerable individuals from severe disease should be a priority. Abstract: Following the easing of lockdown measures in many sub-Saharan African countries, coronavirus disease 2019 (COVID-19) cases have been on the rise. As the transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative agent of COVID-19, may be difficult to stop in these settings, we propose that the existing COVID-19 prevention strategies aimed at reducing overall transmission are complemented with more targeted strategies to protect people at risk of severe COVID-19 disease. We suggest investigating the feasibility, acceptability, and efficacy of distributing COVID-19 prevention kits to households with persons at increased risk of severe COVID-19 disease.